Evidences of language contact in Arequipa: the loncco poems - Guajardo Castro, Alejandra Martina (2015)
In this study we introduce the analysis’ results of a sample lexicon found in traditional poems ("loncco poems") for the Spanish variety spoken in the province of Arequipa. These results show the presence of non-Spanish roots that could correspond to some of the languages that were in contact at the arrival of the Spanish explorers to the valley. The results reinforce the theory of a Puquina language presence in the area, followed by Aimara expansion and then a later presence of the Quechua language.